ANALISIS KADAR PM10 DAN KARBON MONOKSIDA (CO) SERTA KELUHAN GANGGUAN PERNAFASAN AKUT PADA PETUGAS DINAS PERHUBUNGAN TERMINAL AMPLAS MEDAN TAHUN 2014 - ERNA VERONIKA SINAGA; devi nuraini santi; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
One of the most potential air pollution resources come from the transportation sector (60-80%), such as carbon monoxide (CO) and PM10. The existence of carbon monoxide and PM10 in the air can cause health problems, especially respiratory disorders for people who breathe it.The purpose of this study is to analyze the levels of PM10 and Carbon Monoxide in the air of the Amplas Terminal Medan. Then to find out of the characteristicsof the respondents and acute respiratory disturbanceswhich was felt by Transport Department officers in Terminal Amplas.This is a descriptive research. This study used total sampling technique, and the population as many as 81 respondents. Data PM10 and Carbon Monoxide levels obtained by direct measurement in Terminal Amplas. Then, acute respiratorydisturbancesdata obtained by interviewed the Transport Department officers in AmplasTerminal.Air measurement result showed that the levels of PM10 and carbon monoxide in the Amplas Terminal did not exceed the threshold value with the average levels of PM10 is 150 mg/m3 and CO is 29 ppm. Most of respondents (58,3%) who worked in the office of the Transport Department did not have acute respiratory disturbancesand most of respondents (68,1%) who worked outside the office had acute respiratory disturbances.The conclusion of this study is the acute respiratory disturbancesfelt by most of respondents was coughing. There is recommended to Kota Medan Transport Dapertment to regulate the office hours of the Transport Department officers in AmplasTerminal.